PROGRANULIN: IS IT A NEW ADIPOCYTOKINE AT THE CROSSROADS OF OBESITY, METABOLIC SYNDROME AND CANCER? - Donma, Orkide; Donma, Mustafa Metin (LIFE: International Journal of Health and Life-Sciences, 2017)
Progranulin (PGRN) stimulates the proliferation and survival of several cancer cell types. Obesity increases the risk for metabolic as well as cardiovascular diseases, and is linked to an increased incidence and aggressiveness of various cancers. Prepubertal morbid obese (MO) children and those with metabolic syndrome (MetS)(MO+MetS)were included in our studies. World Health Organization age- and sex-dependent body mass index percentile tables were used for the classification of obesity. MetS criteria were defined. Anthropometric measurements, blood pressure values, lipid and glucose metabolism–related parameters, obesity-related adipocytokines were determined. Statistical evaluations were performed. Our studies have pointed out an increasing trend going from MO towards MO+MetS group in terms of PGRN. Elevated PGRN can contribute to tumour microenvironment, stimulate growth, invasion and metastasis of cancer cells. Children with MetS have the tendency of developing chronic diseases such as cancer in their future lives. Obesity, a major public health problem, increases the risks for many severe chronic diseases. Elevated PGRN levels may promote tumor growth, serve as a potential clinical biomarker in cancer and be associated with the increased cancer risk in children with MetS. As a new molecule, PGRN may provide a new intervention target for molecular treatment options.